Converging clinical and engineering research on neurorehabilitation II : proceedings of the 3rd International Conference on Neurorehabilitation (ICNR2016), October 18-21, 2016, Segovia, Spain /: proceedings of the 3rd International Conference on Neurorehabilitation (ICNR2016), October 18-21, 2016, Segovia, Spain. ([2017]) - Unknown
No abstract available